The evolution of the handball talent care system in Hungary - pilot study - Juhász, B.; Bácsné Bába, É. (STADIUM - Hungarian Journal of Sport Sciences, 2018)
Development of talents care systems plays an important role in handball today. The goal of the Hungarian Handball Association is to ensure that all children of the same age receive the same training throughout the country. The Association recently introduced a standard feed-back education system. The aim of this research was to demonstrate the evolution of the talent care system, especially the innovations introduced by the Association.